A Clinical Study to Evaluate the Efficacy of Khasa Beeja Taila (Seed Oil of Papaver Somniferum Linn.) in Darunaka Vyadhi - Sridhar Anishetty; Metuku Shanthi Swaroop; Merugu Shirisha; A.V.Vasanthi (AYUSHDHARA, 2025)
Darunaka Vyadhi, described under Kshudra Rogas and Kapalagata Rogas in Ayurvedic texts, is closely related to dandruff - a common scalp disorder. It is characterized by scalp flaking, itching, and dryness without visible inflammation. Classical references suggest the use of Khasa Beeja Taila (seed oil of Papaver somniferum Linn.) for managing Darunaka Vyadhi. Aim: To evaluate the efficacy and safety of Khasa Beeja Taila (seed oil of Papaver somniferum Linn.) as an external application in the management of Darunaka Vyadhi (dandruff). Objectives: Primary Objective: To assess the anti-dandruff efficacy of Khasa Beeja Taila based on reduction in Adherent Scalp Flaking Score (ASFS) and 5D Pruritis Scale. Secondary Objective: To evaluate the safety and tolerability of Khasa Beeja Taila through clinical observations and hematological parameters (CBP, ESR). Methods: An open-label, single-arm pilot clinical study was conducted on 30 subjects diagnosed with Darunaka Vyadhi. The intervention involved external application of Khasa Beeja Taila twice weekly for four weeks. Efficacy was assessed using the Adherent Scalp Flaking Score (ASFS), 5D Pruritis Scale, and grading scales for Kandu, Twak Sphutana, Keshabhoomi Rookshata, and Keshachyuti. Safety assessments included Complete Blood Picture (CBP) and Erythrocyte Sedimentation Rate (ESR) evaluations. Results: Statistically significant improvements were noted across all parameters. ASFS and 5D Pruritis Scale showed highly significant reductions (p<0.0001) from baseline to the 4th week. Symptoms like Kandu, Twak Sphutana, Keshabhoomi Rookshata, and Keshachyuti significantly reduced over the treatment period. No adverse effects or significant changes in CBP and ESR were recorded, confirming the safety of the formulation. Conclusion: Khasa Beeja Taila demonstrated significant clinical efficacy and safety in managing Darunaka Vyadhi. The results indicate its potential as a natural remedy for dandruff and related symptoms, warranting further large-scale studies.